Simultaneous abiotic production of greenhouse gases (CO2, CH4, and N2O) in subtropical soils - Liu, Jiangong; Hartmann, Simon Christoph; Keppler, Frank (Journal of geophysical research. Biogeosciences, 2019)
Soils exert considerable influence on the global biogeochemical cycles, but their role in the abiotic production of volatile compounds remains poorly understood. In this study, we demonstrated evidence for the abiotic production of three major greenhouse gases (GHGs), namely carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O), simultaneously in six different subtropical surface soils under thermal treatment at 30 to 90 °C, wetting, and the addition of hydrogen peroxide. This study identified soils as a novel source of N2O through abiotic processes such as thermal treatment and the oxidation of reactive oxygen species. Our results showed that the abiotic production rate of all three GHGs increased exponentially with temperature, while that of CO2 and CH4 increased linearly with hydrogen peroxide concentrations. Wetting of soil samples could further enhance the rate of abiotic CO2 and N2O production in soils. These findings highlight the potential contribution of abiotic processes in the production of GHGs in subtropical soils and help constrain the uncertainties of the global GHG budgets.
Im Titel sind die Zahlen 2 und 4 tief gestellt
Gesehen am 22.08.2019